Degrees of change: between and within population variation in thermal reaction norms of phenology in a viviparous lizard. Issue 10 (19th August 2020) - Cunningham, George D.; While, Geoffrey M.; Olsson, Mats; Ljungström, Gabriella; Wapstra, Erik
Abstract: As the earth warms, populations will be faced with novel environments to which they may not be adapted. In the short term, populations can be buffered against the negative effects, or maximize the beneficial effects, of such environmental change via phenotypic plasticity and, in the longer term, via adaptive evolution. However, the extent and direction of these population‐level responses will be dependent on the degree to which responses vary among the individuals within them (i.e., within population variation in plasticity), which is, itself, likely to vary among populations. Despite this, we have estimates of among‐individual variation in plastic responses across multiple populations for only a few systems. This lack of data limits our ability to predict the consequences of environmental change for population and species persistence accurately. Here, we utilized a 16‐yr data set from climatically distinct populations of the viviparous skink Niveoscincus ocellatus tracking over 1, 200 litters from more than 600 females from each population to examine inter‐ and intrapopulation variability in the response of parturition date to environmental temperature. We found that these populations share a common population‐mean reaction norm but differ in the degree to which reaction norms vary among individuals. These results suggest that even where populations share a common mean‐level response, we cannot assume that they will be affected similarly by altered environmental conditions. If we are to assess how changing climates will impact species and populations accurately, we require estimates of how plastic responses vary both among and within populations.